Sierolomorpha sogdiana spec. nov. from Central Asia, and a World catalogue of Sierolomorphidae (Hymenoptera) - Lelej, Arkady S.; Mokrousov, Mikhail V. (Zootaxa, 2015)
Sierolomorpha sogdiana Lelej & Mokrousov, spec. nov. is described and illustrated from Central Asia (Uzbekistan). A key to the Palaearctic species of Sierolomorpha and a World catalogue of the family Sierolomorphidae (13 species in three genera) are given.